The Relationship between Lifestyle Intervention and Remission of Type 2 Diabetes Mellitus: A Literature Review - Wahyuningtyas, Hibha Mahesti; Triastuti, N. Juni; Aribah, Khansa; Arum, Dyah Ayu Sekar; Aulia, Mutia Arsya; Anggrahini, Witrishya (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Background: Type 2 diabetes mellitus is a complex and long-term metabolic illness characterized by hyperglycemia, which is brought on by both insulin resistance and decreased insulin production. Type 2 diabetes mellitus may occur for a variety of reasons, including genetics, high amounts of free fatty acids, and beta-cell malfunction. Weight loss, remission, and an improved quality of life were all outcomes of lifestyle treatment for type 2 diabetes mellitus, which centered on regular physical exercise and nutritious diet. Aim: This study aims to investigate the impact of lifestyle changes on the remission of type 2 diabetes mellitus. Method: This article uses a literature review methodology, with a search of international literature through PubMed, Science Direct, and Google Scholar databases with inclusion and exclusion criteria applied. This review follows the PRISMA chart. Results: To examine the existing literature and put the construction of the research procedure in context, preliminary reviews were searched in the PubMed, Google Scholar, database, as well as ScienceDirect. Five writers have spent time since the database's creation exploring the correlation between lifestyle factors and type 2 diabetes episodes or remissions. Efforts to control food consumption, exercise, and cellular app use Lifestyle interventions, such as programs that provide mentorship, may influence the incidence and remission of type 2 diabetes mellitus. Conclusion: There have been promising results in the treatment and even remission of type 2 diabetes mellitus using lifestyle intervention such as diet intake control program, physical activity, monitoring by smartphone application, and mentor support.